LONG-TERM RESEARCH ASSESSING IN THE HUMANITIES: A CASE STUDY - Anna Chesnokova; Sonia Zyngier; Willie van Peer (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
It is common practice in academic research projects to present final assessment by means of reporting and evaluating results. More often than not, these reports tend to focus on the quantity and quality of the knowledge acquired, and very little (if any) attention is given to the impact the research may have had on the researchers themselves. In an institutional setting where students participate in research, this may be a missing link in the educational chain. The case study described here tried to fill this gap by showing the changes effected by a project investigating literature and language from a multicultural perspective. More than stimulating research by students in different countries, it aimed at helping them become autonomous researchers using empirical methods. We argue that instead of lectures and seminars, the educational quality of the humanities will be greatly enhanced if we turn to our students doing research themselves. We counter the argument that students are not able to do so with reference to a ten-year project we were engaged in, together with our students, between our three universities. We describe the methods along which our students cooperated with each other in conceptualizing, carrying out and reporting on their research. Feedback from 53 participants indicates that not only did the project motivate them to pursue further academic degrees, but the skills they acquired considerably influenced their future in many different fields. Though the design of this study does not allow us to determine any causality in the effects of the program, we argue that the results are nevertheless highly suggestive of the program's both motivational and intellectual success.